2018
DOI: 10.1037/fam0000431
|View full text |Cite
|
Sign up to set email alerts
|

Intervention effects on reflectivity explain change in positive parenting in military families with young children.

Abstract: Military families with young children often experience stress related to the unique circumstances of military families (e.g., deployment), and there is a need for interventions that are specifically tailored to military families with young children. The Strong Military Families (SMF) intervention responds to this need, and consists of two versions: A Multifamily Group (N = 34), and a Homebased psychoeducational written material program (N = 42; treated as the comparison group in this report). The Multifamily G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Positive parenting refers to practices, including consistent discipline, praise, and monitoring (Ryan, O'Farrelly, & Ramchandani, 2017). Positive parenting behavior is regarded as an effective parenting method for diverse populations such as military families, (Julian et al, 2018), parents of children with autism (Zand et al, 2018), and children with callous-unemotional traits (Clark & Frick, 2018). Positive parenting behavior promotes the child's well-being by ensuring a safe environment, engaging the child in learning activities, using appropriate discipline, having realistic expectations of the child, and promoting self-care in the parent (Sanders, Markie-Dadds, Tully, & Bor, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Positive parenting refers to practices, including consistent discipline, praise, and monitoring (Ryan, O'Farrelly, & Ramchandani, 2017). Positive parenting behavior is regarded as an effective parenting method for diverse populations such as military families, (Julian et al, 2018), parents of children with autism (Zand et al, 2018), and children with callous-unemotional traits (Clark & Frick, 2018). Positive parenting behavior promotes the child's well-being by ensuring a safe environment, engaging the child in learning activities, using appropriate discipline, having realistic expectations of the child, and promoting self-care in the parent (Sanders, Markie-Dadds, Tully, & Bor, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that intervention effects for both mother and child affect and behavior were found across both parent-reported and observational measures. Although the broad body of research on family and child development routinely incorporates observational measures of parent–child interaction into their study designs, the vast majority of military family research relies on parent- and child-report (for exceptions see [ 28 , 50 ]). That parents receiving FOCUS-EC (as compared to parents in OPE) demonstrated greater improvements in observed behaviors during parent–child interactions provides stronger support for FOCUS-EC intervention efficacy than parent-report measures alone, because they obviate the possibility of shared method variance.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies with a comparison group reported outcomes related to marriage and family. Three of these studied interventions specifically aimed at marriage (Baddeley and Pennebaker, 2011) or parenting (Julian et al, 2018a;Pinna et al, 2017) In brief, a multifamily therapy group (Julian et al, 2018a) did not have significant effects at two months, while the ADAPT program had significant effects for mothers but not fathers . A brief relationship-focused expressive-writing program had significant effects on marital satisfaction at one month (Baddeley and Pennebaker, 2011), as did stress-management training one year postintervention (controlling for combat exposure) (McKibben et al, 2009).…”
Section: Marriage and Family Outcomesmentioning
confidence: 99%
“…A cohort study published in three articles (Dodge et al, 2018;Julian et al, 2018a;Julian et al, 2018b) reported on Strong Military Families, a parenting intervention delivered in ten sessions via group therapy with other parents and one to three individual sessions. The program teaches stress-management skills and ways to respond to children appropriately.…”
Section: Family Interventionsmentioning
confidence: 99%